Oil Extraction and Production of A Biodiesel Using Vegetable Oil Derived From Algae (Scenedesmus dimorphus) - Prastowo, Indro (Universitas Ahmad Dahlan, 2013)
Biodiesel is a biofuel which is projected to substitute diesel oil.Â Keyword: Scenedesmus dimosphus, biodiesel, sand, n-hexane